Determining the biomass fraction of mixed waste fuels: A comparison of existing industry and 14C-based methodologies. (January 2015) - Muir, G.K.P.; Hayward, S.; Tripney, B.G.; Cook, G.T.; Naysmith, P.; Herbert, B.M.J.; Garnett, M.H; Wilkinson, M.
Highlights: Compares industry standard and 14 C methods for determining bioenergy content of MSW. Differences quantified through study at an operational energy from waste plant. Manual sort and selective dissolution are unreliable measures of feedstock bioenergy. 14 C methods (esp. AMS) improve precision and reliability of bioenergy determination. Implications for electricity generators and regulators for award of bio-incentives. Abstract: 14 C analysis of flue gas by accelerator mass spectrometry (AMS) and liquid scintillation counting (LSC) were used to determine the biomass fraction of mixed waste at an operational energy-from-waste (EfW) plant. Results were converted to bioenergy (% total) using mathematical algorithms and assessed against existing industry methodologies which involve manual sorting and selective dissolution (SD) of feedstock. Simultaneous determinations using flue gas showed excellent agreement: 44.8 ± 2.7% for AMS and 44.6 ± 12.3% for LSC. Comparable bioenergy results were obtained using a feedstock manual sort procedure (41.4%), whilst a procedure based on selective dissolution of representative waste material is reported as 75.5% (no errors quoted). 14 C techniques present significant advantages in data acquisition, precision and reliability for both electricity generator and industry regulator.